Insecticidal Activity Of Mangrove Plants Against Spodoptera Litura - P. Arockia Mary Fernandez; K. Sivaraman; R. Karthika; S. Ramesh Kumar (Revista Electronica de Veterinaria)
This study investigates the insecticidal properties of mangrove plants against Spodoptera litura, a notorious pest that significantly affects agricultural crops. Mangrove plants, known for their unique phytochemical composition, are evaluated for their potential as natural insecticides. The research focuses on the effectiveness of extracts from various mangrove species, assessing both the toxicity and repellent effects on S. litura larvae. Through bioassay-guided fractionation and analysis, promising candidates for organic pest control are identified. The results suggest that certain mangrove extracts exhibit significant insecticidal activity, providing a sustainable alternative to chemical pesticides.